1990
DOI: 10.1007/bf00685423
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the Belgian Society of Medical Oncology with single-administration 5 g/m2 ifosfamide with mesna as second- or third-line therapy in advanced breast cancer

Abstract: In an ongoing phase II trial conducted in advanced breast cancer, we tested a therapy schedule consisting of continuous, 24-h infusion of 5 g/m2 ifosfamide (IFO) in 3 1 dextrose saline with mesna (MSN), repeated every 3 weeks until disease progression. Since September 1988, 16 heavily pretreated patients with advanced disease (11 with visceral lesions) considered refractory to standard chemotherapy (regimens always including cyclophosphamide) have been included. Objective partial remissions were observed in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…These response rates are comparable to other studies utilizing ifosfamide in combination chemotherapy in MBC. 16,[20][21][22][23] Although there was a better response in the ifosfamide-doxorubicin group (75% vs 23%; P = 0.0046), the pre-treatment characteristics in the paclitaxel group were worse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These response rates are comparable to other studies utilizing ifosfamide in combination chemotherapy in MBC. 16,[20][21][22][23] Although there was a better response in the ifosfamide-doxorubicin group (75% vs 23%; P = 0.0046), the pre-treatment characteristics in the paclitaxel group were worse.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Thirdly, in clinical studies, ifosfamide has demonstrated efficacy in advanced breast carcinoma. 16,[20][21][22][23] Although to date there is no conclusive evidence that ifosfamide is superior to cyclophosphamide in the treatment of breast cancer, taken together, we believed it rational to use ifosfamide-based mobilization in our cohort of heavily pre-treated patients.…”
mentioning
confidence: 99%